Decreased portal vein flow during Kawasaki disease in a liver transplant patient. Issue 5 (18th October 2013) - Wakiya, Taiichi; Urahashi, Taizen; Ihara, Yoshiyuki; Sanada, Yukihiro; Yamada, Naoya; Okada, Noriki; Hakamada, Kenichi; Mizuta, Koichi
Abstract Abnormalities of liver function tests are frequently documented in patients with Kawasaki disease, but the mechanism responsible for this has not yet been established. Described herein is the case of a 1‐year‐10‐month‐old girl who underwent liver transplantation at 11 months of age. Eleven months after transplantation the patient was diagnosed with Kawasaki disease, which was associated with some portal flow reduction, and received i.v. immunoglobulin, after which fever abated with improvement of portal flow to its pre‐fever level. Abnormalities of liver function tests in Kawasaki disease patients may occur as a result of inflammation of both the biliary and portal systems. There are no reports on the potential relationship between Kawasaki disease and the portal vein, and accumulation of further data is necessary to better examine this relationship.